Hermit Crabs from North Australian and Eastern Indonesian waters (Crustacea Decapoda: Anomura: Paguroidea) collected during the 1975 Alpha Helix expedition - Haig, J.; Ball, E.E. (Records of the Australian Museum, 1988)
Fifty-two species of hermit crabs of the families Coenobitidae, Diogenidae and Paguridae were collected in the Arafura Sea and in Maluku (Moluccas), Indonesia. Five of these species were previously unrecorded from the Arafura Sea and Torres Strait. At the Banda Islands. where the major part of the collecting was done, 34 out of 37 species are reported for the first time. The collection included 18 new records for Seram and 14 for Saparua. Four new species are described from maluku. Live colour notes and information on natural history are presented for most of the species in the collection, and associations are noted with anemones, rhizocephalans, cirolanid and parasitic isopods, copepods, a shrimp and a polychaete.
This paper contains numerous records for 'East African Coast'. These have not been entered, as the same information, but more precise, is repeated in a more recent paper by the senior author.